2021
DOI: 10.1177/17456916211014196
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Odor Persuasion: The Incorporation of Olfactory Cues in Virtual Environments for Personalized Relaxation

Abstract: Olfaction is the most ancient sense and is directly connected with emotional areas in the brain. It gives rise to perception linked to emotion both in everyday life and in memory-recall activities. Despite its emotional primacy in perception and its role in sampling the real physical world, olfaction is rarely used in clinical psychological settings because it relies on stimuli that are difficult to deliver. However, recent developments in virtual-reality tools are creating novel possibilities for the engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Considering the impact of customization on anxiety and on engaging users in the virtual scenarios, another important aspect that needs to be considered is the opportunity to introduce customized stimuli based on the personal life experience of each participant in the virtual environment. As an example, introducing olfactory stimuli could be another essential aspect to enhance the sense of realism, immersion, and presence in the virtual scenarios [69,70]. A further limitation of this study is the possible exclusion of people who are not familiar with social media.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…Considering the impact of customization on anxiety and on engaging users in the virtual scenarios, another important aspect that needs to be considered is the opportunity to introduce customized stimuli based on the personal life experience of each participant in the virtual environment. As an example, introducing olfactory stimuli could be another essential aspect to enhance the sense of realism, immersion, and presence in the virtual scenarios [69,70]. A further limitation of this study is the possible exclusion of people who are not familiar with social media.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…VR technologies typically engage only two sensesvision and audition-limiting the user's virtual experience. 18 Recent research explores the impact of stimulating additional senses on feelings of presence, immersion, user engagement and overall VR experience. [19][20][21][22][23][24] Scents evoke experiences not solely influenced by cortical elaboration, 7 25 26 activating emotion-related contents or experiences almost automatically.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Their strong association with autobiographical memories allows personalisation of VR settings based on users’ past experiences and needs to enhance relaxation and positive emotional states. 18 Despite extensive evidence on how smell influences mood, stress and anxiety, 25–27 few VR applications and studies have explored olfactory stimulation to improve sensory experiences. 19 28 Notably, one study demonstrated that aversive and unpleasant scents, 19 or simultaneous stimulation of multiple senses (ie, hearing, touch, smell) in VR can heighten feelings of presence, improving outcomes in exposure therapy for specific phobias and post-traumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%
“… Cooper et al (2018) suggested that multisensory feedback cues effectively provide additional information to improve overall task performance and user-perceived presence. Pizzoli et al (2021) reported that olfactory cues can trigger distant memories, reduce the cognitive load required to re-evoke memories and experiences, and help learners relax. However, other studies have shown no significant effect of cues on cognitive load ( Albus et al, 2021 ) or posttest performance ( Hwang and Shin, 2018 ) for learning in virtual reality environments.…”
Section: Introductionmentioning
confidence: 99%